Exclusive breastfeeding and low birth weight as risk factors of stunting in under-five children: A case-control study in Darul Imarah Sub-District, Aceh Besar, Indonesia - Rauzatul Izzah; Aripin Ahmad; Dini Junita; Syuja’ Rafiqi Arifin (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2021)
Stunting refers to children’s growth and development disorders and is affected by chronic nutrient deficiency, repeated infections, and a lack of stimulation during the first 1000 days of their life. This study aimed to examine the effects of breastfeeding and birth weight on the incidence of stunting in under-five children. This case-control study design involved 116 under-five children: 53 children in the case group and 53 children in the control group. This study was conducted in Darul Imarah Community Health Center, Aceh Besar. The data on characteristics, early breastfeeding initiation, exclusive breastfeeding, and breastfeeding duration were collected using the interview method. Meanwhile, the data on birth weight was collected from birth records in the MCH book. Finally, the data on stunting were collected using the anthropometric measurements determined by the HAZ index based on the z-score. A child would have categorized as stunted if the z-score value had been <-2 SD. The collected data were then analyzed using the bivariate and multivariate analyses and the binary logistic regression test at a 95% confidence level. The results showed that exclusive breastfeeding and LBW were risk factors of stunting in under-five children. Children without exclusive breastfeeding had 4.57 times as great risk of stunting as those with exclusive breastfeeding (OR = 4.57; 95% CI; 1.57-13.27). Moreover, children born with low birth weight had 9.43 times as great risk of stunting as those born with normal weight (OR = 9.43; 95% CI; 3.54-25.12). Education and promotion are needed to increase exclusive breastfeeding and improve pregnant women’s health to prevent a low birth weight of babies and reduce the incidence of stunting since the early stage.